EFFECT OF GROWTH REGULATORS ON THE FORMATION OF POTATO (SOLANUM TUBEROSUM L.) MICRO-PLANTS IN VITRO - Asakaviciute, Rita (Potato Journal, 2023)
ABSTRACT: Effect of growth regulators IAR (indole-3-acetic acid) and kinetin (6-furfuryl aminopurine) on length andmass formation of micro-plants of different maturity table potatoes (Solanum tuberosum L.) varieties was evaluated. Thevarieties of different maturity group included were very early ‘VB Venta’, early ‘Goda’, medium early ‘VB Meda’ and verylate ‘VB Aista’. Microplant explants were grown in modified MS nutrient medium with different concentrations of growthregulators.. The concentration of 1.75 ml/l of auxin resulted in significant increase in length and weight of the micro-plantwith highest micro plant growth (10.03± 0.96 cm) and mass (0.218 ± 0.09 g) formation in var ‘VB Meda’ compared to leastgrowth in VB Venta’ (6.2 ± 0.75 cm). Kinetin at concentration of 0.8 ml/l resulted in longest micro-plants formation by ‘VBMeda’ variety (9.03 ± 0.18 cm) and the smallest by ‘VB Venta’ (5.20 ± 0.15 cm) explants.